"Bitch, You Got What You Deserved!": Violation and Violence in Sex Buyer Reviews of Legal Brothels. (December 2018) - Jovanovski, Natalie; Tyler, Meagan
In this article, we use feminist critical discourse analysis to examine online brothel reviews (148 reviews and 2, 424 reply posts) of sex buyers in the context of debates surrounding harm minimization. Our findings show that sex buyers actively construct and normalize narratives of sexual violation and violence against women in licensed brothels through their language, referencing objectification, unsafe sex practices, and, in more extreme cases, rape to create a sense of community with other punters. Through this analysis, we challenge existing assumptions about harm minimization in systems of prostitution, which are legalized or fully decriminalized.